2018
DOI: 10.1038/s41386-018-0088-7
|View full text |Cite
|
Sign up to set email alerts
|

Burst activation of dopamine neurons produces prolonged post-burst availability of actively released dopamine

Abstract: Both phasic and tonic modes of neurotransmission are implicated in critical functions assigned to dopamine. In learning, for example, sub-second phasic responses of ventral tegmental area (VTA) dopamine neurons to salient events serve as teaching signals, but learning is also interrupted by dopamine antagonists administered minutes after training. Our findings bridge the multiple timescales of dopamine neurotransmission by demonstrating that burst stimulation of VTA dopamine neurons produces a prolonged post-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 86 publications
1
33
0
Order By: Relevance
“…The VTA receives major inhibitory GABAergic innervation from the nucleus accumbens as well as other areas in the brain ( Jhou et al., 2009a ; Jhou et al., 2009b ) that controls their patterns in firing ( Paladini and Tepper, 1999 ; Lobb et al., 2010 ) and contributes to burst activation and prolonged activity of DA neurons in the nucleus accumbens and prefrontal cortex ( Paladini et al., 2003 ; Jhou et al., 2009a ; Lobb et al., 2010 ; Morikawa and Paladini, 2011 ; Lohani et al., 2018 ). Since burst-firing can result in increased efficacy and enhanced neurotransmitter release in the presynaptic terminal ( Fisher et al., 1997 ; Floresco et al., 2003 ), GABAergic regulation of DA bursting activity is one way to modulate reward-related memories.…”
Section: Reward Memorymentioning
confidence: 99%
“…The VTA receives major inhibitory GABAergic innervation from the nucleus accumbens as well as other areas in the brain ( Jhou et al., 2009a ; Jhou et al., 2009b ) that controls their patterns in firing ( Paladini and Tepper, 1999 ; Lobb et al., 2010 ) and contributes to burst activation and prolonged activity of DA neurons in the nucleus accumbens and prefrontal cortex ( Paladini et al., 2003 ; Jhou et al., 2009a ; Lobb et al., 2010 ; Morikawa and Paladini, 2011 ; Lohani et al., 2018 ). Since burst-firing can result in increased efficacy and enhanced neurotransmitter release in the presynaptic terminal ( Fisher et al., 1997 ; Floresco et al., 2003 ), GABAergic regulation of DA bursting activity is one way to modulate reward-related memories.…”
Section: Reward Memorymentioning
confidence: 99%
“…Tonic dopamine has been suggested to reflect an average reward signal computed by slow averaging phasic prediction error signals (Niv et al, 2007): cues that have been associated with higher reward expectancies induce larger phasic positive prediction errors resulting in transient increases in tonic dopamine (Phillips and Wightman, 2004; Tobler et al, 2005). Although it has often been suggested that tonic and phasic dopamine are mediated by distinct mechanisms (Floresco et al, 2003; Bromberg-Martin et al, 2010), recent data demonstrated that phasic dopamine could trigger secondary events that increase tonic activation of dopamine levels (Lohani et al, 2018). It is therefore tempting to think that phasic dopamine signaling associated with higher reward expectancies or action values in context-specific perceived control, could influence general perceived control reflected by changes in tonic dopamine levels.…”
Section: Reward Rate Tonic Dopamine and (General) Perceived Controlmentioning
confidence: 99%
“…Prior work has suggested that cortical inputs in response to task-related cues (i.e., phasiclike responses) regulates VTA engagement . Furthermore, recent rodent research shows that phasic increases in dopamine signaling can increase statedependent engagement of the mesolimbic system for prolonged periods of time (Lohani et al, 2018). These findings suggest that age-related differences in the cortical detection of task-relevant cues may be associated with downstream engagement of statedependent functional coupling.…”
Section: Significance Statementmentioning
confidence: 91%
“…Previous research has demonstrated that the detection of behavioral cues by cortex regulate the functional engagement of the VTA (Murty et al, 2017) and VTA-NAcc coupling (Ballard et al, 2011) and that phasic engagement of the VTA can lead to prolonged activation of mesolimbic systems (Lohani et al, 2018). Given that adolescence may be associated with enhanced sensitivity to goal-relevant information in the environment, we characterized relationships between cue-related activation and our state-dependent increases in VTA-NAcc coupling.…”
Section: Moderators Of State-dependent Neurodevelopmentmentioning
confidence: 99%